Cationic ordering and Dielectric Relaxation in a New Series of Double Perovskite BaNdCoXO6 (X = Nb, Sb and Ta). (2015) - Bharti, Chandrahas; Bhadra, Nilanjana; Sen, A.; Chanda, Sadhan; Sinha, T.P.
Abstract: Three new double perovskites oxides have been synthesized using solid state reaction technique. XRD, SEM, EDAX, FTIR and impedance spectroscopy are used to analyze the structural and electrical data for all three compounds.